1997
DOI: 10.1016/s0550-3213(97)00068-0
|View full text |Cite
|
Sign up to set email alerts
|

Gauge-independent resummed gluon self-energy in hot QCD

Abstract: The pinch technique (PT) is applied to obtain the gauge-independent resummed gluon self-energy in a hot Yang-Mills gas. Calculation is performed at one-loop level in linear gauges which preserve rotational invariance and the resummed propagators and vertices are used. The effective gluon self-energy, which is obtained as the sum of the resummed gluon self-energy and the resummed pinch contributions, is not only gaugeindependent but also satisfies the transversality relation. Using this gauge-independent effect… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…Let us mention a few. There have been several application in the area of finite temperature field theory, starting with the early work by Cornwall and collaborators [162,191], the calculation of the plasmon decay constant by Nadkarni [240], the gauge-independent thermal β function computed by Sasaki [241,242], and the work on magnetic screening for the quark-gluon plasma by Alexanian and Nair [243]. In addition, the explicit one-loop PT calculations in the context of the Coulomb and temporal axial gauges have been presented by Passera and Sasaki in [244].…”
Section: Discussionmentioning
confidence: 99%
“…Let us mention a few. There have been several application in the area of finite temperature field theory, starting with the early work by Cornwall and collaborators [162,191], the calculation of the plasmon decay constant by Nadkarni [240], the gauge-independent thermal β function computed by Sasaki [241,242], and the work on magnetic screening for the quark-gluon plasma by Alexanian and Nair [243]. In addition, the explicit one-loop PT calculations in the context of the Coulomb and temporal axial gauges have been presented by Passera and Sasaki in [244].…”
Section: Discussionmentioning
confidence: 99%
“…Hence it is not consistent to stop the calculation at one-loop order for soft internal momenta, and the resummed propagator and the vertices [14] must be used to obtain the complete leading contribution. The PT algorithm still works even when we use the resummed propagator and the vertices [26]. It can be shown that the resummed effective gluon self-energy obtained in the framework of PT is gauge-independent and that, using this effective gluon self-energy, we can obtain the correct thermal β function in the leading order.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…This means, the coupling constant has a strong dependence on the vertex function [15,16]. Also, the dependence of coupling constant on the gauge was investigated in [17,18]. Braaten and Pisarski [19] introduced significant ideas like hard thermal loops and, using it, they presented resummation of QCD thermal perturbation theory.…”
Section: Introductionmentioning
confidence: 99%